Question Number 122624 by Ar Brandon last updated on 18/Nov/20
$$\mathrm{Prove}\:\mathrm{the}\:\mathrm{equality}\:: \\ $$$$\mathrm{n}!=\underset{\mathrm{k}=\mathrm{0}} {\overset{\mathrm{n}} {\sum}}\left(−\mathrm{1}\right)^{\mathrm{k}} \begin{pmatrix}{\mathrm{n}}\\{\mathrm{k}}\end{pmatrix}\left(\mathrm{n}−\mathrm{k}\right)^{\mathrm{n}} \\ $$
Answered by mindispower last updated on 18/Nov/20
$${let}\:{f}\left({x},{y}\right)={e}^{{y}} \left({e}^{{y}} −{x}\right)^{{n}} \\ $$$${f}\left({x},{y}\right)={e}^{{y}} \left[\underset{{k}=\mathrm{0}} {\overset{{n}} {\sum}}\left(−{x}\right)^{{k}} {C}_{{k}} ^{{n}} {e}^{\left({n}−{k}\right){y}} \right] \\ $$$$=\underset{{k}=\mathrm{0}} {\overset{{n}} {\sum}}{e}^{\left({n}+\mathrm{1}−{k}\right){y}} \left(−\mathrm{1}\right)^{{k}} {x}^{{k}} {C}_{{k}} ^{{n}} \\ $$$${f}\left(\mathrm{1},{y}\right)=\underset{{k}=\mathrm{0}} {\overset{{n}} {\sum}}{e}^{\left({n}+\mathrm{1}−{k}\right){y}} \left(−\mathrm{1}\right)^{{k}} {C}_{{n}} ^{{k}} \\ $$$${let}\partial_{{y}} ^{{k}} {f}\left(\mathrm{1},{y}\right)\:{bee}\:{k}\:{derivate}\:{f}\:{over}\:{y} \\ $$$${we}\:{want}\:\partial_{{y}} ^{{n}} {f}\left(\mathrm{1},\mathrm{0}\right) \\ $$$$\partial_{{y}} ^{{n}} {f}\left(\mathrm{1},{y}\right)=\underset{{k}\leqslant{n}} {\sum}\left({n}+\mathrm{1}−{k}\right)^{{n}} {e}^{\left({n}+\mathrm{1}−{k}\right){y}} \left(−\mathrm{1}\right)^{{k}} {C}_{{n}} ^{{k}} \\ $$$$\partial_{{y}} ^{{n}} {f}\left(\mathrm{1},\mathrm{0}\right)=\underset{{k}\leqslant{n}} {\sum}\left({n}+\mathrm{1}−{k}\right)^{{n}} \left(−\mathrm{1}\right)^{{k}} {C}_{{n}} ^{{k}} \\ $$$${f}\left(\mathrm{1},{y}\right)={e}^{{y}} \left({e}^{{y}} −\mathrm{1}\right)^{{n}} \\ $$$$={e}^{{y}} \left({e}^{\frac{{y}}{\mathrm{2}}} \left({e}^{\frac{{y}}{\mathrm{2}}} −{e}^{−\frac{{y}}{\mathrm{2}}} \right)\right)^{{n}} \\ $$$$={e}^{\left(\mathrm{1}+\frac{{n}}{\mathrm{2}}\right){y}} \mathrm{2}^{{n}} {sh}^{{n}} \left(\frac{{y}}{\mathrm{2}}\right)={g}\left(\frac{{y}}{\mathrm{2}}\right)={f}\left(\mathrm{1},{y}\right) \\ $$$${let}\:\frac{{y}}{\mathrm{2}}={z} \\ $$$${g}\left({z}\right)={h}\left({y}\right),\frac{\partial{h}}{\partial{y}}=\frac{\partial{h}}{\partial{z}}.\frac{\partial{z}}{\partial{y}}=\frac{\partial{g}}{\partial{z}}\:\:.\frac{\mathrm{1}}{\mathrm{2}} \\ $$$$\Rightarrow\partial^{{n}} {h}\left({y}\right)=\frac{\mathrm{1}}{\mathrm{2}^{{n}} }.\frac{\partial^{{n}} {g}}{\partial{z}^{{n}} } \\ $$$$\Rightarrow\partial_{{y}} ^{{n}} {f}\left(\mathrm{1},{y}\right)\mid_{{y}=\mathrm{0}} =\partial_{{z}} ^{{n}} {e}^{\left(\mathrm{2}+{n}\right){z}} {sh}^{{n}} \left({z}\right)\mid_{{z}=\mathrm{0}} \\ $$$${we}\:{show}\:{that}\:\forall{k}<{n}\:\:\partial_{{x}} ^{{k}} {sh}^{{n}} \left({x}\right)\mid_{{x}=\mathrm{0}} =\mathrm{0}..{E} \\ $$$$\partial_{{x}} {sh}^{{n}} \left({x}\right)={nch}\left({x}\right){sh}^{{n}−\mathrm{1}} \left({x}\right) \\ $$$${we}\:{know}\:{sh}\left(\mathrm{0}\right)=\mathrm{0} \\ $$$${all}\:{sh}^{{i}} \left({x}\right)\mid{x}=\mathrm{0}\:{give}\:{zero}\:{only}\:{i}=\mathrm{0} \\ $$$${but}\:{derivate}\:{k}<{n}\:{the}\:{least}\:{power}\:{of}\:{sh}\:{is}\:{n}−{k}\geqslant\mathrm{1} \\ $$$$\Rightarrow\:{we}\:{have}\:{all}\:{power}\:{of}\:{sh}^{{m}} \left({x}\right),{m}\in\left[{n}−{k},{n}\right] \\ $$$$=\mathrm{0} \\ $$$$\Rightarrow\partial_{{z}} ^{{n}} {e}^{\mathrm{2}+{n}} {sh}^{{n}} \left({z}\right)=\Sigma{C}_{{n}} ^{{k}} \left({e}^{\left(\mathrm{2}+{n}\right){z}} \:\:\right)^{\left({n}−{k}\right)} {sh}^{{n}} \left({z}\right)^{\left({k}\right)} \\ $$$${by}\:{proposition}?{E}? \\ $$$${we}\:{now}\:{that} \\ $$$${the}\:{only}\:{facteur}\:{we}\:{want} \\ $$$${isC}_{{n}} ^{{n}} {e}^{\left(\mathrm{2}+{n}\right){z}} \left({sh}^{{n}} \left({z}\right)\right)^{\left({n}\right)} \mid_{{z}=\mathrm{0}} \\ $$$${sh}^{{n}} \left({z}\right)^{\left({n}\right)} =\left({nch}\left({z}\right){sh}^{{n}−\mathrm{1}} \left({z}\right)\right)^{{n}−\mathrm{1}} ..{apply}\:{E}\:{againe} \\ $$$${we}\:{want}\:{nch}\left({z}\right)\left({sh}^{{n}−\mathrm{1}} \left({z}\right)\right)^{{n}−\mathrm{1}} \\ $$$$={n}\left({ch}\left({z}\right)\left({n}−\mathrm{1}\right){ch}\left({z}\right)\left({sh}^{{n}−\mathrm{2}} \left({z}\right)\right)^{{n}−\mathrm{2}} …..\right. \\ $$$$={n}\left({n}−\mathrm{1}\right)\left({n}−\mathrm{2}\right)……..\left({n}−\left({n}−\mathrm{1}\right)\right)\left({sh}^{{n}−\left({n}−\mathrm{1}\right.} \left({z}\right)\right)^{\left({n}−\left({n}−\mathrm{1}\right)\right)} \\ $$$$=\left({n}\right)!.\left({sh}\left({z}\right)\right)^{'} \mid_{{z}=\mathrm{0}} \\ $$$$={n}!{ch}\left(\mathrm{0}\right)={n}! \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$